Pengaruh Kualitas Pelayanan Dan Kepercayaan Konsumen Terhadap Keputusan Pembelian Online - Faradila, Aida; Doloksaribu, Tio Arriela; Fitriany, Erika Yuniar; Kristiani, Defliana; Choirrudin, Mohammad Fachri; Kristiana, Rinda Syeyla (JURNAL EKONOMI, MANAJEMEN, BISNIS, DAN SOSIAL (EMBISS), 2024)
This research aims to determine the influence of service quality and consumer trust on online purchases at Lestari Olshop. This method uses descriptive quantitative methods, validity tests, reliability tests, classical assumption tests, multiple regression analysis, hypothesis testing with partial (t test) and simultaneous (F test). The research results show that there is a positive influence between service quality on online purchasing decisions at Lestari Olshop. There is a positive influence between consumer trust in online purchasing decisions at Lestari Olshop. Together there is a positive influence between service quality and consumer trust on online purchasing decisions at Lestari Olshop. The conclusion is that Lestari Olshop has a positive influence on service quality and consumer trust. Future researchers can develop this research by adding other variables such as: promotions and prices which can influence purchasing decisions and can use qualitative research methods by examining the variables regarding purchasing decisions more deeply